СОЦИАЛЬНАЯ ПСИХОЛОГИЯ ЗДОРОВЬЯ: ПОДХОДЫ И ПЕРСПЕКТИВЫ ИССЛЕДОВАНИЯ - Карамян, М.Х. (SCIENCE and SOCIETY, 2018)
The key problems of social health psychology are considered in the article. It is shown that the study of social psychological factors of valuable attitude towards health is important for working out of health education programs.